Outcomes of 1, 327 patients operated on through twelve multispecialty surgical volunteerism missions: A retrospective cohort study. (December 2018) - Latifi, Rifat; Rivera, Renato; Gachabayov, Mahir; Borja Chiong, Maria Melinda; Noyes, R. Dirk; Kleinmann, Michael; Baluyot, Fancy S.; Tilley, Elizabeth; Samson, David; El-Menyar, Ayman
Abstract: Background: Surgical volunteer missions (SVMs) have become a popular approach for reducing the burden of surgical disease worldwide. The aim of this study was to evaluate the outcomes of 12 surgical missions between 2006 and 2018 from the mission entitled "Operation Giving Back Bohol" Tagbilaran, Philippines and discuss the lessons learned during these missions in particular seven challenges that every volunteer surgeon should be familiar with. Methods: This was a retrospective descriptive study of prospectively collected data on all patients treated during one SVM. The data collected included gender, age, diagnosis, types of surgeries performed, and perioperative adverse events. Results: During the study period 1327 operations were performed (842 females (63.4%) and 485 males (36.6%); (male-to-female ratio 0.59); mean age 37 ± 18 years. The majority of operations were for thyroid disease (31.6%), followed by hernia (17.3%), hysterectomies/salpingo-oophorectomies (12.2%), soft tissue tumors (9.9%), cleft lip/palate repairs (7.2%), breast (6.4%), gallbladder disease (4.7%), cataract (2.9%), parotid masses (1.4%) and others (6.4%). For each mission, there were an average 5.5 days of operating, performing a median of 105.5 (80–148) cases per mission. There were 27 complications (2%), of which, 22 were postoperative bleeding and two temporary tracheostomies. The mortality rate was 0.15% (2/1327). In one patient, the family withdrew care following compassionate last ditch effort thyroidectomy for advanced cancer and one patient died as a result of intracranial bleeding from a brain tumor, which was unrecognized before mastectomy. Conclusions: Surgical volunteerism missions are safe and valuable in lessening the burden of surgical disease globally when performed in an organized fashion and with continuity of care. However, there is need for standardization of surgical care provided during SVMs and creation of a world-wide database of all SVMs, and each surgeon and others who participate in these mission should be familiar with critical elements and challenges for the successful mission. Highlights: Surgical volunteerism missions are safe and valuable in lessening the burden of surgical disease globally when performed in an organized fashion and with continuity of care. Postoperative mortality rate in surgical mission was 0.15%. There is need for standardization of surgical care provided during surgical missions.